Evaluating the bioactivity and biocompatibility of nylon coated ultra-high molecular weight polyethylene (UHMWPE) - Hassanein, Nancy (AUC Knowledge Fountain, 2019)
Ultra-high molecular weight polyethylene (UHMWPE) semi crystalline biomaterial is one of the gold standard materials that are used as a bearing surface in total joint replacement surgeries. However, wear particles generated by UHMWPE due to the relative motion between the different components of the bearing, would eventually result in osteolysis and implant failure. For this, many attempts to enhance the properties of UHMWPE were done, including coating the UHMWPE with nylon 6,6 which was reported to improve its mechanical properties and biocompatibility. In this study, the antibacterial activity, moisture and SBF absorption, pH effect, bioactivity, biocompatibility and wound healing ability of the nylon coated in contrast to the uncoated UHMWPE were assessed. The results have shown that the coated UHMWPE was more effective (P<0.001) than the uncoated UHMWPE regarding bacterial (Staphylococcus aureus and Escherichia coli) growth inhibition. Moreover, coated UHMWPE demonstrated superiority over the uncoated UHMWPE; by absorbing less moisture of both simulated body fluid and lactated Ringer's solution and by rendering the pH of simulated body fluid (SBF) less acidic. Chemical analysis of the nylon coated UHMWPE by FTIR, and morphological assessments by SEM confirmed the absence of hydroxyapatite layer and hence the inability of the nylon coated UHMWPE to be osteoconductive. The assessment of the U2-OS cell viability using MTT assay has suggested that both materials appear to not cause cell cytotoxicity and may be accelerating the cellular proliferation after 72 hours when compared to the control sample. For wound healing, nylon coated UHMWPE proved its ability to be a better orthopedic suture than the uncoated sample and control by showing a better wound closure percentage. These interdisciplinary approaches have given us the chance to investigate different features of nylon coated UHMWPE, which is a promising tool to enhance bearing surfaces in total joint arthroplasties.